Hypermassive black holes have faint broad and narrow emission lines. Issue 3 (10th July 2020) - Bhat, Harshitha K; Chakravorty, Susmita; Sengupta, Dhrubojyoti; Elvis, Martin; Datta, Sudeb Ranjan; Roy, Nirupam; Bertemes, Caroline; Ferland, Gary; Ezhikode, Savithri H
ABSTRACT: The extreme ultraviolet region (EUV) provides most of the ionization that creates the high equivalent width (EW) broad and narrow emission lines (BELs and NELs) of quasars. Spectra of hypermassive Schwarzschild black holes (HMBHs; M BH ≥ 10 10 M⊙ ) with α-discs, decline rapidly in the EUV suggesting much lower EWs. Model spectra for BHs of mass 10 6 –10 12 M⊙ and accretion rates 0.03 ≤ L bol / L Edd ≤ 1.0 were input to the cloudy photoionization code. BELs become ∼100 times weaker in EW from M BH ∼ 10 8 M⊙ to M BH ∼ 10 10 M⊙ . The high-ionization BELs (O vi 1034 Å, C iv 1549 Å, and He ii 1640 Å) decline in EW from M BH ≥ 10 6 M⊙, reproducing the Baldwin effect, but regain EW for M BH ≥ 10 10 M⊙ . The low-ionization lines (Mg ii 2798 Å, H β 4861 Å, and H α 6563 Å) remain weak. Lines for maximally spinning HMBHs behave similarly. Line ratio diagrams for the BELs show that high O vi /H β and low C iv /H α may pick out HMBH, although O vi is often hard to observe. In NEL BPT diagrams, HMBHs lie among star-forming regions, except for highly spinning, high accretion rate HMBHs. In summary, the BELs expected from HMBHs would be hard to detect using the current optical facilities. From 100 to 10 12 M⊙, the emission lines used to detect active galactic nuclei (AGNs) only have high EW in the 10 6 –10 9 M⊙ window, where most AGNs are found. This selection effect may be distorting reported distributions of M BH .